Propose a new firefly-fast learning network model based intrusion-detection system - Badran, Mohammed Falih; Moorthy, Kohbalan; Zukifi, Nor Saradatul Akmar; Mohamad, Mohd Saberi; Deris, Safaai; Md.Sahar, Nan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Currently, effective Intrusion-detection systems (IDS) still represent one of the important security tools. However, hybrid models based on the IDS achieve better results compared with intrusion detection based on a single algorithm. But even so, the hybrid models based on traditional algorithms still face different limitations. This work is focused on providing two main goals; firstly, analysis based on the main methods and limitations of the most-recent hybrid model-based on intrusion detection, secondly, to propose a novel hybrid IDS model called FA-FLN based on the Firefly algorithm and Fast Learning Network.